2021
DOI: 10.1186/s40663-021-00288-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of climate, tree diversity and local human disturbance determine the stability of dry Afromontane forests

Abstract: Background Anthropogenic disturbances are increasingly affecting the vitality of tropical dry forests. The future condition of this important biome will depend on its capability to resist and recover from these disturbances. So far, the temporal stability of dryland forests is rarely studied, even though identifying the important factors associated with the stability of the dryland forests could serve as a basis for forest management and restoration. Methodology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 83 publications
0
0
0
Order By: Relevance
“…Consequently, the dry Afromontane forest is highly sensitive to climate change in combination with other factors. For example, [10] revealed that a combination of climate, topographic factors, and local human disturbance controlled the stability of dry Afromontane forests. Furthermore, the dry Afromontane conifer forest, as well as the rest of the forest of the country, is at risk due to the expansion of agricultural land as a result of population pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the dry Afromontane forest is highly sensitive to climate change in combination with other factors. For example, [10] revealed that a combination of climate, topographic factors, and local human disturbance controlled the stability of dry Afromontane forests. Furthermore, the dry Afromontane conifer forest, as well as the rest of the forest of the country, is at risk due to the expansion of agricultural land as a result of population pressure.…”
Section: Introductionmentioning
confidence: 99%